(untitled) - SETIAWAN, AGUNG (Jurnal Ilmu Manajemen (JIM), 2013)
Nowadays human resources has an important position foran organization or company. As performed by many existing Hospital,Kanjuruhan Hospital Malang also continue to improve theperformance of its employees particularly well in all aspects ofservice. Malang Kanjuruhan Hospital is a government hospital locatedin Malang regency. Its presence is an important part of the publicservice that aims to provide the best possible service to thecommunity. In order to realize the objectives of the hospital as apublic servant. The results of analysis show that: 1) Work disciplinedoes not affect the performance of either simultaneously or partially,2) Motivation partially positive significant effect on employeeperformance.Keywords: work discipline, motivation, empleyee performent.